Catalyst-free N-methylation of 3-methylxanthine with dimethyl carbonate in water: green synthesis of theobromine. (16th June 2022) - Yang, Hansen; Wang, Zhimiao; An, Hualiang; Yang, Qiusheng; Xue, Wei; Li, Fang; Wang, Yanji
Abstract : 3-Methylxanthine conversion of 89.9% with 98.2% theobromine selectivity. Abstract : Theobromine is an important pharmaceutical intermediate and food additive. We have developed a green method for theobromine synthesis, namely catalyst-free methylation of 3-methylxanthine with dimethyl carbonate (DMC). The effects of various solvents on the reaction were investigated; H2 O was found to be the most appropriate solvent. The bond energies of C–O in DMC and N–H in 3-methylxanthine were calculated at the M06-2x/6-311G(d, p) level, and the role of the solvent was examined theoretically. The use of H2 O as the solvent and the effects of DMC hydrolysis on the reaction were investigated. The results show that DMC hydrolysis was, to some extent, beneficial to theobromine synthesis. The reaction conditions were optimized. When the molar ratio of DMC to 3-methylxanthine was 11 : 1 and the 3-methylxanthine dosage was 0.1 g per mL-H2 O, reaction at 160 °C for 9 h gave a 3-methylxanthine conversion of 89.9% with 98.2% theobromine selectivity.